Autonomy in fertility: a personalist analysis of sexual and reproductive rights from a historical-bioethical perspective - Bustamante-Barahona, Pía Poulett; Fuentes-Valdebenito, Nicolás Matías (Universidad Hemisferios, 2025)
Fertility has historically been understood as a reality imbued with symbolic, spiritual, and social meaning. However, the rise of contemporary reproductive biotechnologies, together with the consolidation of a stance of radical and absolute autonomy in the field of sexual and reproductive rights, has transformed how human fertility is conceived and addressed. This article offers a historical and bioethical review, tracing conceptions from a sacred view of fertility to its current instrumentalization and clinical reduction. On this basis, it argues that the principle of autonomy-when interpreted through an individualistic and technicized lens-tends to detach fertility from embodiment and relationality, even though these are constitutive of its very nature. In response, a critique is proposed from the perspective of personalist bioethics, emphasizing the need to reintegrate the bodily and relational dimensions of the person into any ethical deliberation concerning fertility. The article concludes by proposing a holistic, co-responsible understanding of fertility, situated as a constitutive aspect of the person that calls for care, and not grounded solely in decisions based on individual autonomy or confined to the exclusive sphere of women's experience.